2010
DOI: 10.3390/su2123639
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Compressed Earth Bricks: Assessing Erosion Resistance Using the Modified Spray Testing

Abstract: The discussion in this paper is part of research directed at establishing optimal stabilization strategy for compressed bricks. The deployment context for the use of the compressed bricks was Dar es Salaam (Tanzania) where manually fabricated bricks are increasingly being used in low cost housing units. This discussion specifically focuses on strategies that can be used to counter deterioration due to wind-driven rain erosion. The impact of using cement, lime, fiber and a commercial stabilizing fluid was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 3 publications
0
30
0
Order By: Relevance
“…As such, it can be concluded that when 0.25% of PET fibers are added to the earth blocks, the cement percentage should be kept at 10% or higher. (4) All 24 specimens tested for surface erosion met the requirements, and none of the blocks recorded erosion greater than 0.04 in/min, which was designated as an upper limit by Obonyo et al [35]. Cement stabilization contributed to the reduction of surface erosion, with 0.1% reduction per percent of cement addition.…”
Section: Effect Of Inclusion Of Recycled Plastic Fiber Reinforcement mentioning
confidence: 93%
See 1 more Smart Citation
“…As such, it can be concluded that when 0.25% of PET fibers are added to the earth blocks, the cement percentage should be kept at 10% or higher. (4) All 24 specimens tested for surface erosion met the requirements, and none of the blocks recorded erosion greater than 0.04 in/min, which was designated as an upper limit by Obonyo et al [35]. Cement stabilization contributed to the reduction of surface erosion, with 0.1% reduction per percent of cement addition.…”
Section: Effect Of Inclusion Of Recycled Plastic Fiber Reinforcement mentioning
confidence: 93%
“…Because the amount of water added during block production is directly related to the block strength, it was kept as low as possible, resulting in a water-to-binder ratio of 25%. Table 4 presents further information on the design of mixtures as well as results for the following tests: Absorption Test Results per ASTM C67-11 [34] and water pressure related surface erosion tests based on the procedure presented in Obonyo et al [35]. The following conclusions are drawn from the test data and visual observations during testing:…”
Section: Effect Of Inclusion Of Recycled Plastic Fiber Reinforcement mentioning
confidence: 99%
“…Over the same time period, the chemical reactions that occur when fiber is included in the mix reduce Carbon content by over 1/3 while significantly increasing the Oxygen, Silica and Calcium content. Although previous research recommended the inclusion of both lime and Fiber for the case study context (see [5]), it is also clear that their use could result in both desirable and undesirable effects depending on how the mineralization of the organic inclusions affect hydration-based chemical reactions. The performance of compressed earth bricks can be optimized through establishing a direct link between these changes and desirable physical or mechanical properties.…”
Section: Results and Findingsmentioning
confidence: 99%
“…In a previous publication [5], the author presented preliminary data capturing changes in the earthen masonry microstructure that can be linked to exposure-related deterioration. The author tabulated chemical characterization quantifying changes after samples had been aged through being immersed in water and exposed to 100 °C temperatures in an oven for 7 days.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation